Benzofuran-fused phosphole : synthesis, electronic, and electroluminescence properties - Chen, Hui (2013)
A synthetic route to novel benzofuran-fused phosphole derivatives 3–5 is described. These compounds showed optical and electrochemical properties that differ from their benzothiophene analog. Preliminary results show that 4 can be used as an emitter in OLEDs, illustrating the potential of these new compounds for opto-electronic applications.